Advances in catalyst metals and supports for lignin hydrogenation - GAO Jie; ZHANG Yitian; LUO Gang; CAO Yang*; ZHANG Shicheng* (能源环境保护)
Developing technology for the utilization of lignin resources to obtain high-value aromatic chemicals will not only increase the economic value of lignin but also help achieve the "double carbon" goal. Considerable research efforts have been directed toward investigating lignin hydrogenation. Based on the different types of hydrogen donors, lignin hydrogenation can be divided into exogenous hydrogen (including molecular hydrogen, alcohol solvents, or formic acid) and endogenous hydrogen supply (lignin self-transfer hydrogenolysis). Lignin hydrogenation offers notable advantages, such as high product yields and relatively simple product compositions. However, harsh reaction conditions have prompted the development of efficient hydrogenation catalysts. The focus of research is on regulating the active metal and support centers of hydrogenation catalysts to improve the activity. Through extensive studies of numerous lignin hydrogenation catalysts, advances in lignin hydrogenation depolymerization have been summarized. The influence of metal oxygen affinity, along with the different catalytic effects of various sizes of metal on the product distribution of lignin depolymerization through exogenous hydrogen supply and self-transfer hydrogenolysis, is analyzed. Additionally, the impacts of acidity, surface functional groups, and porous and defective structures of supports on catalytic performance are elucidated. Finally, the prospective outlook on the future of lignin resource utilization is presented.